The Impact of Adverse Drug Reaction (ADR) Monitoring Systems on Enhancing Drug Safety - Samran (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Adverse drug reactions (ADRs) are a serious concern in drug use, potentially endangering patient safety if not properly monitored. Objective: This study aimed to determine the incidence of ADRs and identify the drugs causing ADRs among hospitalized patients at RSUD Drs. H. Amri Tambunan, Deli Serdang Regency. Research Methods: a descriptive non-experimental study with a retrospective approach was conducted. Data were collected from medical records between September 2022 and February 2023. Analysis was performed descriptively using the Naranjo scale. Results: a total of 139 suspected ADR cases were identified. Based on the Naranjo scale, 1 case (0.72%) was definite, 86 cases (61.87%) were probable, and 52 cases (37.41%) were possible ADRs. Antibiotics (61.87%) were the most common drug class causing ADRs, with ciprofloxacin and levofloxacin being the main drugs. The most common ADR manifestation was redness (23.74%). Dexamethasone (41.73%) was the most frequently administered medication to treat ADRs. Conclusion: The incidence of ADRs at RSUD Drs. H. Amri Tambunan remains relatively high, predominantly linked to antibiotic use. Strengthening the adverse drug reaction monitoring system through enhanced reporting, healthcare worker training, and regular antibiotic use evaluations is crucial to improving patient safety.